Vitamin D-mediated regulation of CYP21A2 transcription — A novel mechanism for vitamin D action - Lundqvist, Johan; Wikvall, Kjell; Norlin, Maria (Biochimica et biophysica acta, 2012)
1α,25-Dihydroxyvitamin D3 has recently been reported to decrease expression and activity of CYP21A2. In this paper, we have studied the mechanisms for the 1α,25-dihydroxyvitamin D3-mediated effect on CYP21A2 transcriptional rate. We have studied the effects of 1α,25-dihydroxyvitamin D3 using luciferase reporter constructs containing different lengths of the CYP21A2 promoter. These constructs were transfected into cell lines derived from human and mouse adrenal cortex. The mechanism for the effects of vitamin D on the CYP21A2 promoter was studied using chromatin immunoprecipitation assay, mutagenesis and gene silencing by siRNA. 1α,25-Dihydroxyvitamin D3 was found to alter the promoter activity via a VDR-mediated mechanism, including the comodulators VDR interacting repressor (VDIR) and Williams syndrome transcription factor (WSTF). The involvement of comodulator VDIR was confirmed by gene silencing. We identified a vitamin D response element in the CYP21A2 promoter. Interaction between this novel response element and VDR, WSTF and VDIR was shown by chromatin immunoprecipitation assay. When this sequence was deleted, the effect of 1α,25-dihydroxyvitamin D3 was abolished, indicating that this sequence in the CYP21A2 promoter functions as a vitamin D response element. Interestingly, an altered balance between nuclear receptors and comodulators reversed the suppressing effect of vitamin D to a stimulatory effect. This paper reports data important for the understanding of the mechanisms for vitamin D-mediated suppression of gene expression as well as for the vitamin D-mediated effects on CYP21A2. We report a novel mechanism for effects of 1α,25-dihydroxyvitamin D3. ► The transcriptional rate of CYP21A2 is downregulated by 1α,25-dihydroxyvitamin D3. ► The effect is mediated by nuclear receptor VDR and comodulators VDIR and WSTF. ► The expression level of comodulators may shift the suppression to stimulation. ► This paper reports a functional VDRE in the CYP21A2 promoter. ► Our data indicate a novel mechanism for vitamin D action.